Trends in unsuitability for blood donation in the Brazilian Amazon - Rivera Chavez, Graciela Marleny; Barbosa, Anderson Nogueira; Pontes, Gemilson Soares (Frontiers in Public Health, 2022)
Introduction Sociodemographic and behavioral factors are usually associated with the unsuitability to donate blood. Understanding the reasons behind the exclusion of blood bags is crucial for reducing donor deferral rates. This study aimed to characterize the profile of unsuitable donors in the Blood Center of the northern Brazilian state of Amazonas. Methods This is a retrospective study, based on documentary analysis of electronic medical records obtained in the Hematology and Hemotherapy Foundation of the state of Amazonas. This study included all individuals with complete medical records (n = 87,463) who tried to donate blood between 2017 and 2019. Results The overall rate of donor unsuitability was 19.12% (n = 16,627) and the main reason was poor nutritional status (15.17%), followed by chronic health problems (11.40%), risky sexual behavior (9.5%) and exposure to risk (8.83%). High blood pressure figured as the leading cause of unsuitability among chronic health conditions (85.19%), while having sex with multiple partners (92.63%) was the main sexual risk behavior. The risk of exposure to malaria was responsible for 99.45% of unsuitability among those who were unsuitable due to exposure to risk factors. Deferral rates were associated with increasing age and replacement donation, which was the predominant type of donation. Women had the highest rates of unsuitability, mainly during the first donation (37.04%). Discussion This study provides the first known profile of blood donor unsuitability in the Brazilian Amazon and raises awareness of the region-specific needs that must be met to reduce blood donor unsuitability.